Formulation of the problem of mathematical modeling of accommodation of basic stations of cellular communication in residential territories for students of it-directions of preparation - Bogdanova A.V.; Korostelev A.A.; Mukhutdinov R.H.; Shakirova I.A.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The relevance of considering the issues of mathematical modeling in the preparation of students of IT-directions is due, primarily, to the trends in the development of the sector of artificial intelligence, modeling in general. Today it is clear that the use of mathematical models for the study and prediction of various processes and conditions, can significantly reduce the cost of introducing new technologies and products, as well as significantly reduce the time for implementation and testing. This led us to the conclusion that close attention should be paid in teaching students of the IT areas of training both in modeling methods and in setting modeling problems, analyzing source data and building interconnections in designing models. The article discusses the general concept of the formulation of the problem of mathematical modeling on the example of modeling the location of cellular base stations in residential areas. The basic principles of estimation are considered, each of which can be detailed depending on the tasks set to the required depth. Based on the selected criteria and characteristics, KPIs and a system of indicators can be compiled, which can be used to solve various problems of electromagnetic hazard analysis. Currently, we can only talk about intermediate results of the study. The study is ongoing at the time of this article. However, the results can be successfully used in teaching students of IT-areas of training in mathematical modeling. BEIESP.